The magic of thinking big - Schwartz, David Joseph (2015)
The timeless and practical advice in The Magic of Thinking Big "Believe Big, "says Schwartz. "The size of your success is determined by the size of your belief. Think little goals and expect little achievements. Think big goals and win big success. Remember this, too! Big ideas and big plans are often easier -- certainly no more difficult - than small ideas and small plans."
Believe you can succeed & you will -- Cure yourself of excusitis, the failure disease -- Build confidence & destroy fear -- How to think big -- How to think & dream creatively -- You are what you think you are -- Manage your environment: go first class -- Make your attitudes your allies -- Think right toward people -- Get the action habit -- How to turn defeat into victory -- Use goals to help you grow -- How to think like a leader.
Includes index.
Keywords: Success; Self-confidence.; Level of aspiration; Level of aspiration; Self-confidence.; Success; Self-help publications